CubeSat GPS Observation of Traveling Ionospheric Disturbances After the 2022 Hunga‐Tonga Hunga‐Ha'apai Volcanic Eruption and Its Potential Use for Tsunami Warning. Issue 4 (11th April 2023) - Han, Shin‐Chan; McClusky, Simon; Mikesell, T. Dylan; Rolland, Lucie; Okal, Emile; Benson, Craig
Abstract: Multiple passages of the atmospheric (Lamb) waves were recorded globally after the Hunga Tonga‐Hunga Ha'apai (HTHH) volcanic eruption on 15 January 2022. The waves perturbed the ionosphere and produced traveling ionospheric disturbances (TIDs) that were observed from the ground network of Global Positioning System (GPS) receivers. This study presents new observations of TIDs at higher altitudes (>550 km) from CubeSat GPS tracking data. The satellite sampling along many CubeSat orbits enable to map broader spatio‐temporal patterns of the TID propagation compared to ground receivers. Due to the larger spatial coverage over a shorter period of time, the CubeSat measurements provide complementary information to stationary ground receivers. We found that the amplitude of the HTHH‐induced ionospheric perturbations at high altitudes (>550 km) are as large as 10 TECU (1 TECU = 10 16 electrons/m 2 ) in slant total electron content between CubeSats and GPS satellites. The TIDs traveled along with the Lamb waves and were recorded by CubeSats above India 12 hr after the eruption and at the antipode of the eruption 16 hr after. These suggest that the ionospheric disturbances reached to the high altitudes and traveled globally as a speed of ∼350 m/s. The TIDs were also detected by CubeSats above the Australian continent several hours before the (conventional) tsunami made landfall on the Australian coasts. We discuss a new opportunity to study the upper ionosphere and its coupling with the solid Earth and to develop advanced monitoring systems of geohazards by the advent of low‐cost small satellite technology. Plain Language Summary: CubeSat of a shoe box size is a low‐cost technology that can be used as a platform of various science payloads. The outputs become increasingly reliable and relevant not only to the science community, but also to the public. Global Positioning System receivers are being widely used to locate CubeSats and experiment on the atmosphere via the radio wave refraction. This study reports CubeSat GPS observations of the atmospheric perturbations after the Hunga Tonga‐Hunga Ha'apai (HTHH) volcanic eruption on 15 January 2022. Triggered by the HTHH explosion, the atmospheric waves propagated throughout the entire globe and vertically to the ionosphere populated with electrons. The CubeSat GPS receivers detected significant disturbances in the upper ionosphere (>550 km altitudes) traveling with the atmospheric waves, reaching even to the antipode of the volcano 16 hr after the eruption. It was also noticed that such ionospheric disturbances were detected above the continents before the tsunami waves make landfall. The study suggests new opportunity to explore how the upper atmosphere responds to extreme events occurred on the solid Earth and demonstrates how the atmospheric sensing based on affordable small satellite constellation can be used to monitor extreme events such as volcanic eruptions, tsunamis, and earthquakes. Key Points: A constellation of CubeSats detected traveling ionospheric disturbances (TIDs) caused by the Hunga‐Tonga Hunga‐Ha'apai volcanic eruption The slant total electron content anomaly at high altitudes was as large as 10 TECU and remained significant at the antipode 16 hr after the eruption suggesting the propagation speed of ∼350 m/s TIDs observed a few hours before the conventional tsunami reach the Australian coasts leave time for tsunami source assessment